STUDY OF HYDROPOWER POTENCY FOR SUPPORTING THE FULFILLMENT OF ENERGY NEEDS IN THE NEW NATIONâS CAPITAL CITY REGION (CASE STUDY: MAHAKAM RIVER REGION) - SYAH BARRAN ROESBIANTO, AZMAN
The ratification of the National Capital City Law (RUU IKN) by The House of Representatives of The Republic of Indonesia is the initial inauguration in the effort to move the nation’s capital from DKI Jakarta. Some of the considerations for this displacement include increasing the level of population density, inequality in regional economic contributions, the crisis of water availability, and the rapid land conversion experienced by Java. This requires that new areas, especially the area of East Kalimantan Province, which is a candidate for the capital city, must meet the basic needs of the community, one of them being in the energy sector. The estimated additional energy of 1,555 MW from existing conditions, can be achieved by water energy with a Hydropower Plant (PLTA) system. As a transition step for NRE-based power plant infrastructure, this is in line with the results of the 26th COP Summit, the Net Zero Emission Indonesia Road Map Program, and the G-20 Summit which all were attended by Indonesia. In addition, this plan is supported by the condition of Indonesia, which is one of the countries with the potential for high surface water availability. Thus, regional readiness needs to be assessed through an assessment of potential hydropower locations in East Kalimantan, especially the Mahakam River Area. The development of a potential site study method is carried out by applying a model in the form of the Soil and Water Assessment Tool (SWAT) which relates the runoff discharge value to a rain event. The use of tools in the form of the SWAT Weather Database can compile various combinations of databases with components such as Climate Forecast System Reanalysis (CFSR) satellite data to fulfill climatology, Tropical Rainfall Measuring Mission (TRMM) satellite data, and observational rain data to fulfill rain values. The results of the model are calibrated against field observation data to obtain a more reliable value. Potential location analysis is based on the discharge value, Digital Elevation Model (DEM), flow direction, and flow accumulation in the study area. The application of a diversion algorithm that analyzes a location is expected to produce potential points that can be a source of energy for power plants. This mapping also presents social aspects in the form of land use considerations to avoid land use confrontations such as the designation of protected areas, population areas, and water transportation routes. The initial power potential value of micro hydropower and mini hydropower located in the Mahakam River Area is 6,471 MW with a total location of 3,160 points. After undergoing filtration on several aspects, the final potential value is 114.39 MW with 41 points. The distribution of potential points tends to be in the upstream area of the WS which has a topography with a large height difference. In the future, this potential value must go through a deeper study, especially in determining the flow and the use of DEM data, which requires an approach to field observations. The value of potential uncertainty cannot be determined in this study, due to limited data and field access. Thus, this research can be used as a prefeasibility study stage which is an initial representation of the water energy potential value of Mahakam River Area.